A Bibliometric and Visualization Analysis of Social Support among College Students: Insights from the Web of Science Core Collection - Jie, Shi; Voon, Siok Ping (HRMARS, 2026)
Based on literature from the Web of Science Core Collection (2015–2025), this study adopts bibliometric methods and uses CiteSpace software to visualize research on social support among college students. It analyzes publication trends, leading authors, institutions, countries, and keyword co-occurrence to clarify the field’s developmental trajectory and identify key research trends. Findings show a steady increase in publications, indicating sustained academic interest. Prominent scholars and institutions are actively contributing, with China and the United States exerting significant international influence and collaboration. Core keywords—social support, mental health, college students, stress, and depression—have formed eight major thematic clusters: perceived social support, depressive symptoms, physical activity, mental health, behavior, peer support, gender differences, and college students. In light of current hotspots, the study outlines future research directions, emphasizing the need for individualized and contextualized approaches to social support, digitalization and platform-based services, dynamic theoretical model development, and practical intervention strategies. These insights aim to guide future academic inquiry and contribute to the deepening and refinement of research on college student social support.